Relationship between prostate cancer gene 3 (PCA3) and characteristics of tumor aggressiveness. Issue 2 (10th July 2012) - Augustin, Herbert; Mayrhofer, Katrin; Pummer, Karl; Mannweiler, Sebastian
Abstract BACKGROUND Data supporting prostate cancer gene 3 (PCA3) as prognostic marker are still inconsistent. With special emphasis to Gleason pattern specific tumor volumes (TVs) the relationships between PCA3 score and different characteristics of tumor aggressiveness were meticulously analyzed. METHODS In 127 patients treated with radical prostatectomy for clinically localized prostate cancer, urinary PCA3 score was quantified using Progensa™ PCA3 assay. Total TV and Gleason patterns' specific tumor volumes (GPTV) were assessed by computer‐assisted planimetry. Spearman's rank correlations coefficients (r) were calculated to assess relationships between PCA3 and TV as well as GPTV. Regression analyses were performed to estimate the relationship between PCA3 and TV as well as non‐organ confined disease. RESULTS Mean patients' age was 60.8 years. Patients showed a mean PSA level of 8.1 ng/ml and a mean PCA3 score of 68.5. PCA3 was not significantly correlated with TV (r = 0.131, P = 0.142). Stratified by Gleason score groups ≤6, 7, and ≥8, PCA3 showed no significant correlations with TV. In a subgroup analysis of 50 patients with different primary and secondary Gleason patterns there was neither a correlation with the primary GPTV (r = 0.071, P = 0.626) nor with the secondary GPTV (r = 0.052, P = 0.722). The PCA3 score was neither an independent predictor for TV nor for non‐organ confined disease. CONCLUSIONS The PCA3 score did not show any significant correlation with TV, primary or secondary GPTV. Moreover, the PCA3 score was not an independent predictor for TV or for non‐organ confined disease. Thus, the PCA3 score had no impact for the prediction of aggressive prostate cancers. Prostate 73: 203–210, 2013. © 2012 Wiley Periodicals, Inc.